Investigation and experiment of radar systems in unmanned arial vehicles-II - Tan, Alvin Wei Hua (2015)
As the world modernizes, radar is useful for many applications not only for military applications but civilian applications such as imaging, mapping and obtaining speed of a car. This report begins with a background of the various types of radar, modulation techniques, antennas and supporting components required to be integrated and work together as one. It is followed by block level system will be discussed to further understand the principle of radar. This report then proceeds on to some problems faced and some solutions to solve it. The knowledge learnt during the progress of the project which is multidisciplinary and hands on in nature and is detailed in this report.